Unification of rules of the international system of units through selfinstructional - Cámara Acero, Andrés (2017)
Objective: The present research aimed to evaluate the effects of the application of self instructional modules on improving levels of unification of the rules of the international system of units of the teachers of the Faculty of Education UNHEVAL 2012. Method: In order to deepen the analysis and interpretation of the results was used quasi-experimental design and using probability sampling was chosen a working group made up of 59 teachers, elementary and secondary education. A experimental groups (16) and control (43) was given a pre-test and post-test of 10 questions, both expressed in the vigesimal system. For statisticians estimate was made using descriptive statistics and for the testing of the hypothesis we applied the chi-square test. Results: From the analysis it follows that the experimental group’s final average is 15, which shows that learning achievement is satisfactory, and the control group with the final average is 11, which shows slight difficulties in the development of planned learning and need further follow and intervention teachers according to their pace and learning style. Conclusions: the level of learning of teachers in the experimental group relative to the unification of the rules of the international system of units at the end of the study, significantly improves the application of self-instructional modules, compared to the control group teachers not received the application.